The Effect of Heat-Killed Candida Albicans and Dentin Powder on the Antibacterial Activity of Chlorhexidine Solution - Mohammadi, Zahed (Iranian Endodontic Journal, 2012)
Introduction: The purpose of this study was to compare the inhibitory effect of heat-killed Candida albicans and dentin powder on the antibacterial activity of chlorhexidine (CHX) against Enterococcus faecalis and Streptococcus sanguis. Materials and Methods: The antibacterial effect of each group was determined by measuring the zone of inhibition diameter in millimeters after incubation at 37°C for 24 hours in a humid atmosphere. Each test was repeated three times. Data were analyzed using ANOVA and Tukey’s test. Results: Results indicated that both heat-killed C. albicans and dentin powder decreased the antibacterial activity of CHX against both tested bacteria significantly (P<0.05). <span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">Conclusion<span style="font-size: 11pt; color: black; font-style: normal; font-family: "Times New Roman","serif"; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: FA;">: In conclusion, both heat-killed Candida albicans and dentin powder reduced the antibacterial activity of CHX significantly.